Лицар чарівних струн (До 90-річчя від дня народження Андрія Бобиря) - Димченко, С. (Народна творчість та етнографія, 2005)
On the basis of facts (reviews, placards, bills, memoirs, references of contemporaries) this article deals with different aspects of incredibly fruitful pedagogical and conductor's activity of the prominent cobzars' connoisseur, talented, unique and virtuoso bandura player Andriy Bobyr.